MEMBACA DAKWAH SUFISTIK DALAM PRODUK BUDAYA POPULER (KAJIAN SEMIOTIKA TERHADAP LIRIK LAGU DEKENGANE PUSAT) - Maskuro, Vina Lailatul (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Music is not only used as a medium of entertainment, but along with the development of the age music is also used as a medium of da'wah by the preachers. There are many music whose lyrics contain da'wah messages, among popular music that contains da'wah messages is the song "Dekengane Pusat". This article aims to examine and understand the message of Sufistic da'wah in the song "Dekengane Pusat". The song "Dekengane Pusat" is the artwork of a musician named Dahlan Efendi, This song was first sung by a dangdut singer named Elsa Safira. In this study, researchers used a qualitative approach with Ferdinand de Saussure's semiotic analysis method using four Saussure concepts, namely signifier and signified, langue and parole, syntagmatic and paradigmatic (associative), synchronic (synchronic) and diachronic (diachronic). The result obtained in this study is that the lyrics of the song "Dekengane Pusat" contain several Sufistic da'wah messages, namely the invitation to repent, the prohibition not to pursue desperately something that cannot be brought to death and how to deal with problems and tests in life